Greeniums in sovereign bond markets - Monika Grzegorczyk; Guntram B. Wolff (Bruegel, 2022)
The total market value of green bonds exceeded half a trillion dollars in 2021 and will increase to 1 trillion by the end of 2022. The growing European green sovereign bond market has a value of close to exteuro147 billion at issuance. We study whether investors price green sovereign bonds differently to normal sovereign bonds. We do not expect to find a so-called 'greenium': the promise attached to green sovereign bonds is rather loosely defined and green and normal sovereign bonds are both backed by the full faith and credit of their respective governments. However, when systematically matching green and normal sovereign bonds using a number of criteria, including date of issuance and maturity, a small greenium can be measured. More research is needed to understand why rational investors do not arbitrage away this greenium.
Keywords: 330